Integrated Strategy Performance: Waste Management Findings at Griyo Mulyo Sidoarjo: Strategi Terpadu dalam Pengelolaan Limbah: Temuan di Griyo Mulyo Sidoarjo - Habibi, Muhammad Rizal; Rodiyah, Isnaini (Indonesian Journal of Public Policy Review, 2025)
General Background: Rapid population growth and urbanization in Sidoarjo Regency, East Java, are increasing waste generation, straining the capacity of the Griyo Mulyo Final Processing Site (TPA). Specific Background: Despite efforts, the TPA experienced overload in 2021, necessitating an immediate and comprehensive strategic overhaul to ensure sustainable waste management. Knowledge Gap: Previous studies often lack a comprehensive strategic framework, while existing management suffers from challenges like low HR competence and technology mismatch. Aims: This study analyzes the strategy of the Environmental and Sanitation Agency (DLHK) in waste management at TPA Griyo Mulyo, based on Jack Kooten's four strategic dimensions. Results: The strategies are integrated: Institutional (TPA-BLUD transformation), Organizational (participatory leadership), Program (TPS3R, volume-based tariffs), and Resource Support (HR training, SIPPAS system), resulting in a 28.2% waste volume reduction (2019-2023). However, limitations persist regarding technology compatibility and staff competency. Novelty: The use of Jack Kooten's four strategic dimensions provides a new, comprehensive framework for evaluating integrated waste management performance in a local government context. Implications: The findings offer a model for local governments to build resilient waste management systems through institutional and technological adaptation, prioritizing human resource development to overcome operational constraints. Highlights: TPA Griyo Mulyo transitioned to a BLUD model to enhance operational flexibility and accountability. Integrated strategies led to a 28.2% reduction in Sidoarjo's annual waste volume from 2019 to 2023. Management remains constrained by HR competency gaps and technology mismatch with local wet waste characteristics. Keywords: Strategy, Waste Management, TPA Griyo Mulyo, Organizational Performance, Resource Support.